MEROKOK DAN EFEKNYA TERHADAP KESEHATAN GIGI DAN RONGGA MULUT - Ni Nengah Sumerti (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Smoking is a risk  factor of patholigic diseases of both locally in the oral cavity and systemic diseases. Oral cavity is the first point of contact of the cigarrete smoke so that it is easily exposed to smoking effect. To inhale cigarrete smoke is the same inhaling more than 4.000 chemical substance dangerous to our health. The aims of the literature study is to identify the various effect of the smoking habbit toward dental  and oral cavity. The local effect due to includes dental caries, dental hygiene, periodontontal  diseases, dental lost, recovery slow down, lesi pre-cancer and cancer within oral cavity. Relevant health personnels need to educate the community members obout the danger of smoking and to motivate the community member to quit smoking and to suggestion to maintain their health.